Effect of FIFA11+ Level 3 on muscular strength and muscular endurance among young adult footballers - Armadi, Ilham; Adnan, Mohd Aizzat; Mohamed, Muhamad Noor; Raja Hussain, Raja Nurul Jannat; Shari, Maisarah; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the effectiveness of the FIFA 11+ Level 3 warm-up programme in enhancing muscular strength and endurance among youth football players compared to traditional routines. Utilizing a controlled trial of 20 male development players, researchers assessed performance using the Handgrip Strength and One-Minute Squat tests before and after the intervention. By analyzing both within-group and between-group changes, the research investigates whether this structured injury-prevention protocol serves as a viable tool for immediate physical performance enhancement in elite youth sports.